The Yard of Wit : Male Creativity and Sexuality, 165-175 - Stephanson, Raymond (Book collections on Project MUSE., 2004)
"Positioning sexuality as a volatile mechanism in the development of creative energy, The Yard of Wit explains why male writers associated their authorial work - both the internal site of creativity and its status in public - with their genitalia and reproductive and erotic acts, and how these gestures functioned in the new marketplace of letters. Using the figure and writings of Alexander Pope as a touchstone, Stephanson offers an inspired reading of an important historical convergence, a double commodification of male creativity and of masculinity as the sexualized male body." "In considering how literary discourses about male creativity are linked to larger cultural formations, this elegant, enlightening book offers new insight into sex and gender, maleness and masculinity, and the intricate relationship between the male body and mind."--Jacket